Early detection of Australian Aboriginal and Torres Strait Islander infants at high risk of adverse neurodevelopmental outcomes at 12 months corrected age: LEAP-CP prospective cohort study protocol. Issue 1 (7th January 2022) - Luke, Carly R; Benfer, Katherine; Mick-Ramsamy, Leeann; Ware, Robert S; Reid, Natasha; Bos, Arend F; Bosanquet, Margot; Boyd, Roslyn N
Abstract : Introduction: Neurodevelopmental disorders (NDD), including cerebral palsy (CP), autism spectrum disorder (ASD) and foetal alcohol spectrum disorder (FASD), are characterised by impaired development of the early central nervous system, impacting cognitive and/or physical function. Early detection of NDD enables infants to be fast-tracked to early intervention services, optimising outcomes. Aboriginal and Torres Strait Islander infants may experience early life factors increasing their risk of neurodevelopmental vulnerability, which persist into later childhood, further compounding the health inequities experienced by First Nations peoples in Australia. The LEAP-CP prospective cohort study will investigate the efficacy of early screening programmes, implemented in Queensland, Australia to earlier identify Aboriginal and Torres Strait Islander infants who are 'at risk' of adverse neurodevelopmental outcomes (NDO) or NDD. Diagnostic accuracy and feasibility of early detection tools for identifying infants 'at risk' of a later diagnosis of adverse NDO or NDD will be determined. Methods and analysis: Aboriginal and/or Torres Strait Islander infants born in Queensland, Australia (birth years 2020–2022) will be invited to participate. Infants aged < 9 months corrected age (CA) will undergo screening using the (1) General Movements Assessment (GMA); (2) Hammersmith Infant Neurological Examination (HINE); (3) Rapid Neurodevelopmental Assessment (RNDA) and (4) Ages and Stages Questionnaire-Aboriginal adaptation (ASQ-TRAK). Developmental outcomes at 12 months CA will be determined for: (1) neurological (HINE); (2) motor (Peabody Developmental Motor Scales 2); (3) cognitive and communication (Bayley Scales of Infant Development III); (4) functional capabilities (Paediatric Evaluation of Disability Inventory-Computer Adaptive Test) and (5) behaviour (Infant Toddler Social and Emotional Assessment). Infants will be classified as typically developing or 'at risk' of an adverse NDO and/or specific NDD based on symptomology using developmental and diagnostic outcomes for (1) CP (2) ASD and (3) FASD. The effects of perinatal, social and environmental factors, caregiver mental health and clinical neuroimaging on NDOs will be investigated. Ethics and dissemination: Ethics approval has been granted by appropriate Queensland ethics committees; Far North Queensland Health Research Ethics Committee (HREC/2019/QCH/50533 (Sep ver 2)-1370), the Townsville HHS Human Research Ethics Committee (HREC/QTHS/56008), the University of Queensland Medical Research Ethics Committee (2020000185/HREC/2019/QCH/50533) and the Children's Health Queensland HHS Human Research Ethics Committee (HREC/20/QCHQ/63906) with governance and support from local First Nations communities. Findings from this study will be disseminated via peer-reviewed publications and conference presentations. Trial registration number: ACTRN12619000969167.